PERILAKU PEZIARAH PADA MAKAM SYEKH YUSUF DI KABUPATEN GOWA - Hamka, Hamka; Manda, Darman; Najamuddin, Najamuddin (Social Landscape Journal, 2024)
This study aims to (i) analyse more deeply the causes of the motivation of pilgrims to visit the Sepulchre of Sheikh Yusuf and (ii) analyse and explain further the shape and behavior of Pilgrims of the Sepulation of Shah Yusuf in Gowa district. The type of research is descriptive by using qualitative approaches with methods of phenomenological analysis, as well as using primary and secondary data. Data analysis techniques include data collection, data reduction, data presentation, conclusion withdrawal and verification. The results of this study show that: (i) Pilgrims may see a visit to the tomb of Sheikh Joseph as an opportunity to purify the soul, improve the quality of life, and spiritual growth. The concept of a baraka or blessing of a sanctuary, as well as love and seeking spiritual enlightenment and obtaining bliss from religious figures. Visiting the Sepulchre of Sheikh Yusuf is also part of the religious identity of individuals and groups. The interaction with the symbols, rituals, and experiences in the tombs reinforces the religious identity of the pilgrims. (ii) The diversity of the forms of pilgrimage performed by pilgrims, as well as reflecting the complexity of relations between religious and cultural values in their religious practice, giving offerings, or following certain ceremonies, as an expression of spiritual need and adherence to religious teachings or social traditions. Emphasis on Peter L. Berger's Theory of Social Construction The ritual of pilgrimage to the tombs of Sheikh Yusuf as a form of externalization, plays a role in preserving and communicating the meaning of religion, as well as building and strengthening the religious identity of individuals and groups.